(untitled) (Cadernos de Sociomuseologia, 2025)
The research consists of an analysis of the way in which the historical museums in the immediate region of Ribeirão Preto, in the countryside of the State of São Paulo, Brazil, represent the different migrant populations in their collections and in their museological communications. Sixteen historical museums located in eleven cities of the selected space were analyzed. The research was carried out in a qualitative-quantity manner, consisting of direct observation, document analysis, questionnaires and interviews. The research hypothesis is that the historical museums of the selected region do not represent the populations that were enslaved in the region in the 19th century, as well as they do not represent migrants from the north and northeast regions of the country in their collections and permanent exhibitions, even though the region of Ribeirão Preto has attracted, over the previous two centuries, thousands of people to work in the coffee sector and, later, in the sugar cane sector. As a result, the ideas of <museum landscape= are presented, synthesizing the scenario of museums in the region, and <museological landscape=, synthesizing the museological communications produced by museums in the region and presented in the context of their opening processes in favor of their communities. Key words: Historical museums, local history, museum landscape, museological landscape, sociomuseology